Diurnal patterns of growth and transient reserves of sink and source tissues are affected by cold nights in barley. (28th February 2020) - Barros, Kallyne A.; Esteves‐Ferreira, Alberto A.; Inaba, Masami; Meally, Helena; Finnan, John; Barth, Susanne; Davis, Seth J.; Sulpice, Ronan
Abstract: Barley is described to mostly use sucrose for night carbon requirements. To understand how the transient carbon is accumulated and utilized in response to cold, barley plants were grown in a combination of cold days and/or nights. Both daytime and night cold reduced growth. Sucrose was the main carbohydrate supplying growth at night, representing 50–60% of the carbon consumed. Under warm days and nights, starch was the second contributor with 26% and malate the third with 15%. Under cold nights, the contribution of starch was severely reduced, due to an inhibition of its synthesis, including under warm days, and malate was the second contributor to C requirements with 24–28% of the total amount of carbon consumed. We propose that malate plays a critical role as an alternative carbon source to sucrose and starch in barley. Hexoses, malate, and sucrose mobilization and starch accumulation were affected in barley elf3 clock mutants, suggesting a clock regulation of their metabolism, without affecting growth and photosynthesis however. Altogether, our data suggest that the mobilization of sucrose and malate and/or barley growth machinery are sensitive to cold. Abstract : Barley uses almost equally sucrose, starch and malate for night growth under optimal growth temperatures. Under cold, mostly sucrose and malate are used, starch synthesis being strongly repressed, even when cold is only applied at night.